Report of The Committee on Panchayati Raj Institutions - Planning Commission (Planning Commission, 1978)
The Cabinet Secretariat in their Resolution No. 14/1/2/77- CF dated 12th December, 1977, appointed the Committee on Panchayati Raj Institutions. The Resolution reads: “The Government accords the highest priority to rural development, so as to increase agricultural production, create employment, eradicate poverty and bring about an all round improvement in the rural economy. The Government considers that the maximum degree of decentralisation, both in planning and in implementation, is necessary for the attainment of these objectives.
Government of India, Ministry of Agriculture and Irrigation